Effect of PAF on polyrnorphonuclear leucocyte plasma membrane polarity: a fluorescence study - A. Kantar; P. L. Giorgi; R. Fiorini (Hindawi Limited, 1993)
The effect of PAF on the plasma membrane polarity of polymorphonuclear leukocytes (PMNs) was investigated by measuring the steady-state fluorescence emission spectra of 2-dimethylamino(6-1auroyl) naphthalene (Laurdan), which is known to be incorporated at the hydrophobic-hydrophilic interface of the bilayer, displaying spectral sensitivity to the polarity of its surrounding. Laurdan shows a marked steady-state emission blue-shift in non-polar solvents, with respect to polar solvents. Our results demonstrate that PAF (10−7 M) induces a blue shift of the fluorescence emission spectra of Laurdan. These changes are blocked in the presence of the PAF antagonist, L-659,989. Our data indicate that the interaction between PAF and PMNs is accompanied by a decrease in polarity in the hydrophobic-hydrophilic interface of the plasma membrane.